Peptic ulcer complications requiring surgery: What has changed in the last 50 years in Turkey - Güzel, Hakan; Kahramanca, Şahin; Şeker, Duray; Özgehan, Gülay; Tunç, Gündüz; Küçükpınar, Tevfik; Kargıcı, Hülagü (Turkish Journal of Gastroenterology, 2014)
Abstract Background/Aims: The incidence and prevalence of peptic ulcer disease has decreased in recent years, but it is not so easy to make the same conclusion when complications of peptic ulcer are taken into consideration. The aim of this study is to determine the time trends in complicated peptic ulcer disease and to state the effects of H2 receptor blockers, proton pump inhibitors (PPI), and H. pylori eradication therapies on these complications. Materials and Methods: This study retrospectively evaluated the patients who were operated on for complications (perforation, bleeding, and obstruction) of peptic ulcer for the last 50 years. Patients were grouped into four groups (G1-G4) according to the dates in which H2 receptor blockers, PPIs, and eradication regimens for H. pylori were introduced The time periods that were studied were: (G1) 1962-1980, (G2) 1981-1990, (G3) 1991-1997, and (G4) 1998-2012. Results: In total, 2953 patients were operated on for complications of peptic ulcer disease, of which 86% of the patients were male. In G1, perforation and obstruction were significantly the most frequent complications (p<0.001), followed by bleeding. In groups G2 and G3, obstruction was still the most frequent complication requiring surgery (p<0.001). In G2 and G3, obstruction was followed by perforation and bleeding, respectively. In G4, perforation was significantly the most frequent complication (p<0.001). Conclusion: From 1962 to 1990 obstruction was the most common complication requiring surgery. In the last decade, perforation became the most common complication. In contrast to reports in the literature, bleeding was the least common complication requiring surgery in Turkey.